„Każdy przecinek w tym konkordacie jest zrobiony za moją osobistą zgodą” – kilka uwag na temat wpływu papieża Piusa XI na treść Konkordatu Polskiego z 1925 roku - Sobczyk, Paweł (Prawo Kanoniczne, 2010)
During the pontificate of Pope Pius XI (1922-1939), a new type of relations emerged between Church and state. The Church, which was confirmed in a number of new international agreements signed in the interwar period, sought to separate itself from the state and to endorse its autonomy and independence. Furthermore, the Holy See wished to guarantee respect for the position of public law, which would be confirmed by international agreement reached between the Church and the particular country, traditionally known as the Concordat. Among Concordats signed by the Holy See during the pontificate of Pope Pius XI, there is the Polish Concordat of 1925, which became the model for many subsequent international agreements. On the content of the Concordat of 1925 many factors had influence: historical, political, legal, religious and social. Among them there is a personal involvement into it of Pope Pius XI, which is difficult to qualify from a scientific point of view. The Pope, who was once a nuncio in Poland and a friend of Marshal Jozef Pilsudski, undoubtedly influenced the content of an international agreement reached after lengthy negotiations between the Holy See and the Polish Republic in 1925. Brachium seculare, the state’s financial assistance, the influance of state authorities on the casting of church positions or article VIII, under which the priests celebrating the liturgy on the national holiday on May 3 had to pray „for the welfare of the Republic and its president”, are just something more than a signum temporis.